Pliny the Elder's world: Natural history, books 2-6 - Plinius Secundus, Gaius 23-79 (Cambridge University Press, 2022)
Pliny's World offers readers a translation of the Natural History's opening books unprecedented for its completeness, accuracy and accessibility. Here, in quirky, often breathless style, Pliny lays the foundation of a hugely influential encyclopedia with coverage of the universe, stars, planets and moon, followed by earth's climate and then its physical and human geography. From Rome as ruling centerpoint, Pliny surveys the known world and its countless peoples in a vast arc from the Atlantic to Sri Lanka, embracing the Danube, Euphrates and Nile lands, Atlas and Caucasus mountains, Germany, Africa, Arabia, India. Passages from later books further illustrating his geographical grasp are appended, on topics as varied as wine, water, trees, birds and fish. Throughout, Pliny's frank expression of strong opinions about religion, distorted human values, abuse of the environment (and more) reveal uncannily modern preoccupations. His work remained an inspirational resource through the Renaissance, and still fascinates today
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Pliny / the Elder / Naturalis historia; Human physiology / Early works to 1800; Medicine, Greek and Roman